Pemanfaatan Media Sosial Untuk Meningkatkan Volume Penjualan Pada Mexalminuz Clothing di Kudus (Studi Kasus: Penggunaan Media Sosial Facebook dan Instagram) - Ayi Muhiban; Ade Wartono (Jurnal EMT KITA, 2022)
Research was conducted at Mexalminuz Clothing in Kudus. The purpose of this study was to find out how much the benefits of social media to increase sales volume at Mexalminuz Clothing in Kudus. The purpose of promotion is to convey information, position the product, persuade consumers to like the product, increase and control sales volume, and can influence consumer spending decisions. If this promotional strategy is carried out properly, it will have a good impact on the sustainability of Mexalminuz Clothing in Kudus because there is quite a lot of potential to introduce products and conduct sales activities through the use of social media Facebook and Instagram. This research is a field research with a qualitative descriptive approach, the data used are primary data and secondary data. With data collection techniques in the form of interviews, observations, questionnaires, and documentation. The population used is 2 managers of Mexalminuz Clothing in Kudus and the sample to see customer responses is 4 people with indicators of respondents making purchases in the last 1 month. The results of this study are advertising using social media Facebook and Instagram, sales promotions using discounts or price reductions, premiums or gifts, trade shows, coupons or vouchers, and product guarantees.